2022
DOI: 10.3389/fnagi.2022.886491
|View full text |Cite
|
Sign up to set email alerts
|

The Instrumental Activities of Daily Living in Parkinson’s Disease Patients Treated by Subthalamic Deep Brain Stimulation

Abstract: BackgroundEveryday functioning and instrumental activities of daily living (IADL) play a vital role in preserving the quality of life in patients with Parkinson’s disease (PD) after deep brain stimulation of the subthalamic nucleus (STN-DBS).ObjectiveThe main goal of the current study was to examine IADL change in pre-and post-surgery of the STN-DBS. We also analyzed the influence of the levodopa equivalent daily dose (LEDD) and global cognitive performance (Dementia Rating Scale; DRS-2) as covariates in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…This study is consistent with previous studies regarding improving motor and quality of life ( Fasano et al, 2010 ; Lahtinen et al, 2020 ; Bove et al, 2021 ; Bezdicek et al, 2022 ; Golfrè Andreasi et al, 2022 ; Zeng et al, 2023 ). It is shown that postoperative Med-off treatment with only STN-DBS improved PD motor compared with preoperative Med-off status.…”
Section: Discussionsupporting
confidence: 93%
“…This study is consistent with previous studies regarding improving motor and quality of life ( Fasano et al, 2010 ; Lahtinen et al, 2020 ; Bove et al, 2021 ; Bezdicek et al, 2022 ; Golfrè Andreasi et al, 2022 ; Zeng et al, 2023 ). It is shown that postoperative Med-off treatment with only STN-DBS improved PD motor compared with preoperative Med-off status.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, by using the correlation analysis of the patient's test index NSE and BI index, it is found that NSE is related to skillful activities such as feeding, dressing, toilet use. Bezdicek et al [21] found that the increase of NSE often represents a greater degree of brain damage and aggravation of symptoms in patients with Parkinson's disease, while the aggravation of central nervous system damage is often closely related to skilled activity, which is consistent with our results. Secondly, our clinical prediction model shows that there is a linear cor- The recuperation of patients' condition is indissociable from the meticulous nursing plan implemented by nursing personnel and the provision of comprehensive health education [22], which is derived from the enhancement of nurs-…”
Section: Discussionsupporting
confidence: 92%